7x+18x-3=5(5x+4)

Simple and best practice solution for 7x+18x-3=5(5x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+18x-3=5(5x+4) equation:



7x+18x-3=5(5x+4)
We move all terms to the left:
7x+18x-3-(5(5x+4))=0
We add all the numbers together, and all the variables
25x-(5(5x+4))-3=0
We calculate terms in parentheses: -(5(5x+4)), so:
5(5x+4)
We multiply parentheses
25x+20
Back to the equation:
-(25x+20)
We get rid of parentheses
25x-25x-20-3=0
We add all the numbers together, and all the variables
-23!=0
There is no solution for this equation

See similar equations:

| (5-6)=t/5+7 | | 10+6w=8w-10 | | 6x+1=2x–19 | | 1/2v-1/3=-4/5 | | 5x+1=6x−6 | | 5.3=c-2.7 | | 15=2b+15 | | 9x+48=5x-16 | | (3x+6)=58 | | 12x+4=17x+2 | | -9(u-6)=-4u+19 | | 7c+15=12c | | (3x-5)=17 | | 7=(5n-8)+6(4+6n) | | -88=-4(1+3r) | | (4x+4)=127 | | 5x+1 = 6x−6 | | n-32/4=2 | | 17-3v+11=-12-8v | | g/3=1.6 | | 21x+44=2(14x+8) | | 2p+14+8p=14 | | 20=2(8-2w)+2(w) | | 4(x−9)=−6x+4 | | x+62=60 | | 266=19p | | 4x+4=127 | | 2/x=3x+4 | | 19+2x=6x+5 | | |2x+4|=|2x-6| | | n+10/2=-3 | | -7x-6+3x=-22. |

Equations solver categories